Central African Republic : First Review Under the Staff-Monitored Program. (IMF Staff Country Reports; Country Report ;, 2022)
The fragile security environment has improved following the attempt by armed groups to seize power at the turn of the year 2021. The reopening of the Douala-Bangui corridor reinvigorated activity and curbed inflationary pressures. The third Covid-19 wave is receding, but vaccination has been slow. President Touadera has launched the Republican dialogue peace initiative alongside the Luanda Road Map spearheaded by neighboring countries. The surrender of a key rebel leader to the International Criminal Court represents a key step in the peace process. Donors have delayed disbursing budget support pending greater transparency in the government's security-related spending. This poses substantial fiscal and social risks given the heavy reliance on budget support. The sharp deterioration in terms of trade, reflecting food and fuel price shocks, compounded by geo-political spillovers, will exacerbate existing vulnerabilities and further erode policy space.